Parental Influence in Early-Onset Childhood Depression: A Case-Based Perspective - Prisnidiawati, Ajeng; Basuki, Shinta Maulydiyah; Karida, Rika Nur; Rasyid, Rezza Dwi Ar; Ridlo, Fairuz; Kasiani, Tutik Nur; Algristian, Hafid (Medicor : Journal of Health Informatics and Health Policy, 2025)
Childhood depression often stems from early-life stressors such as peer bullying and negative parenting. Early- onset depression can have long-term impacts on a child’s emotional and cognitive development. Nevertheless, parental awareness of their crucial role in supporting children’s mental health remains limited. This case report describes the clinical manifestation of depression in a 10-year-old boy, triggered by prolonged bullying and insufficient family support, and explores how parental psychoeducation can facilitate recovery. This research employs a descriptive qualitative case study method, in which data were collected through in-depth clinical interviews with the patient and his parents, as well as direct observation. The initial screening used the Strengths and Difficulties Questionnaire (SDQ) to identify emotional and behavioral concerns. Additionally, semi structured interviews were conducted to explore psychosocial history, school experiences, and parenting style over a four week outpatient period. The child presented with persistent sadness, social withdrawal, hallucinations, and academic pressure, particularly from his grandmother, with clear behavioral changes following continuous bullying at school. Through targeted psychoeducation, the mother adopted a more responsive and non-judgmental parenting approach, leading to gradual emotional improvement in the child, as seen by reduced social isolation and improved emotional expression. This case highlights the critical role of family support and parental psychoeducation as non-pharmacological interventions in early- onset childhood depression, emphasizing the importance of early detection of depressive symptoms and involving families in emotional support strategies to strengthen children’s mental resilience.